Methicillin-resistant Staphylococcus aureus colonization: a three-year prospective study in a neonatal intensive care unit in Italy. - Daniela M Geraci (PLoS ONE, 2014)
BACKGROUND: Methicillin resistant Staphylococcus aureus (MRSA) is a major etiological agent of infection in neonatal intensive care units (NICUs). Routes of entry of this organism can be different and the transmission pathway complex. Colonized neonates are the main endogenous reservoir. METHODS AND RESULTS: We conducted a prospective three-year study on MRSA colonization recruiting 722 neonates admitted between 2009 and 2012. Nasal swabs were cultured weekly and MRSA isolates were submitted to molecular typing. The annual incidence density of acquisition of MRSA ranged from a maximum of 20.2 cases for 1000 patient-days during the first year to a minimum of 8.8 cases in the second one to raise again up to 13.1 cases during the third year. The mean weekly colonization pressure fluctuated from 19.1% in the first year to 13.4% in the second year and 16.8% in the third year. It significantly correlated with the number of MRSA acquisitions in the following week. Overall, 187 (25.9%) subjects tested positive for MRSA. A non multiresistant, tst positive, ST22-MRSA-IVa spa t223 strain proved to be endemic in the NICU, being identified in 166 (88.8%) out of 187 colonized neonates. Sporadic or epidemic occurrence of other strains was detected. CONCLUSIONS: An MRSA strain belonging to the tst1 positive, UK-EMRSA-15/ "Middle Eastern Variant" appeared to be endemic in the NICU under investigation. During the three-year period, substantial changes occurred in case-mix of patients moving towards a higher susceptibility to MRSA colonization. The infection control procedures were able to decrease the colonization rate from more than 40% to approximately 10%, except for an outbreak due to a CA-MRSA strain, ST1-MRSA-IVa, and a transient increase in the colonization prevalence rate coincident with a period of substantial overcrowding of the ward. Active surveillance and molecular typing contributed to obtain a reliable picture of the MRSA dissemination in NICU.